Analysis of the rural community behavior in the Area of Electoral Geography (Case study: Varzaqan county) - Aghil Khaleghi; Hossein Karimzadeh; kuomars Khaodapanah (تحقیقات کاربردی علوم جغرافیایی)
The present research has been carried out to analyze the behavior of the rural community of Varzaqan in the territory of electoral geography and the approach used in it is "spatial-behavioral". Research based on the purpose is practical and in terms of collecting data, it's a mixed type (exploratory design - tool development model). According to the research goal, using the qualitative method, through the phenomenological method, the deep understanding, complexity, detail and texture of the studied phenomena have been studied. Then, using this initial identification (in order to arrive at a generalized result), it was attempted to develop the tool using the SEM. Using a targeted sampling method, the sample size of the first phase is 25, and for the second phase, 32 people are localized. Phenomenological results show that the Electoral Behaviors of rural community in Varzaqan county can be analyzed in three main categories: (a) "geographic features" with the themes of "sense of location, neighborhood impact, and localism"; (b) "individual and social" with the themes of "social stimulus and individual stimulus"; and (c) "political" Themes "Engagement Conditions, Affective Role, Political Orientation, and Religion." This behavior is in accordance with the categories of "geographical and political characteristics" with the "rational choice theory", and in terms of "individual and social" with "the pattern of political economy (wise reformed approach)". Modeling results also show that the variable "geographical features" and "individual and social factors" are at the "significant" threshold and the variable "political factors" is within the "average" threshold; The quality test of the structural model shows that "political agents" and "social factors" have "strong" values and "geographic features" have average values to determine the predictive power of the electoral model.  The general model of the SME shows the goodness of fit in the model and shows its generalizability.